Problems of Modeling the Processes of Audition in the World Psycholinguistics - Лариса Калмикова; Наталія Харченко; Інна Мисан (Психолінгвістика, 2019)
Introduction. The problem of listening comprehension modeling is one of the most debatable in psycholinguistics: so far, in both Western European and American and Eastern European psycholinguistic sciences, the search for the possibility of developing a model of listening as a coherent speech is not stopped. At the same time, various scientific ideas about models and the actual process of modeling are fixed.